2014
DOI: 10.1155/2014/695029
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of, and Patient Satisfaction with, Colonoscopic-Administered Fecal Microbiota Transplantation in Relapsing and Refractory Community- and Hospital-Acquired Clostridium difficile Infection

Abstract: FMT was a highly successful and very acceptable treatment modality for treating both community- and hospital-acquired CDI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 10 publications
0
38
0
1
Order By: Relevance
“…The details and characteristics of the included studies are presented in Table . The 18 selected studies yielded a total of 611 patients . Eleven of 18 studies reported a mean or median age over 60 years; 62.7% (396/611) of patients were female.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The details and characteristics of the included studies are presented in Table . The 18 selected studies yielded a total of 611 patients . Eleven of 18 studies reported a mean or median age over 60 years; 62.7% (396/611) of patients were female.…”
Section: Resultsmentioning
confidence: 99%
“…Only 4 of 18 studies carried out consecutive case recruit‐ment, according to reviewers . While seven studies showed a stratified outcome, all studies had a clear main finding according to reviewers. Other detailed information was clarified in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, we maintain that hospitalization with C. difficile equates with intestinal perturbation of the microbiota. The arguments are (1) C. difficile, although ubiquitous in the environment, occurs almost exclusively in individuals receiving antibiotics, proton pump inhibitors, H 2 receptor antagonists, and other drugs that disrupt the bacterial composition of the gastrointestinal tract (42,43); (2) antibiotic stewardship programs decrease the incidence of CDI through reduction in antibiotic use (44); and, most importantly, (3) restoring the normal gut microbiome in persons with CDI cures the disease (15,45). Although CDI may not be the only instance in which dysbiosis occurs, it is certainly a hallmark indication of intestinal perturbation.…”
Section: Discussionmentioning
confidence: 99%